1987
DOI: 10.1055/s-2007-1020232
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Active Prosthetic Valve Endocarditis. Results in 66 Patients

Abstract: The results of combined medical and surgical management of 66 patients with active prosthetic valve endocarditis (APVE) are analyzed. Between 1970 and 1985, 3510 patients were operative survivors of mitral, aortic or double mitral-aortic valve replacement. Cumulative follow-up was 15,640 patient-years (mean 4.4 years). The overall annual incidence of reoperation for APVE was 0.42 +/- 0.05% (0.34 +/- 0.08% for biological and 0.46 +/- 0.06% for mechanical prostheses, p = n.s.). Early APVE occurred in 21 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 1 publication
0
1
0
3
Order By: Relevance
“…The 5-year survival in our study of PVE patients was only 37% AE 5% (non-PVE 63% AE 5%), which is similar to 30% AE 6% reported by Cortina and colleagues. 18 However, other studies have reported better 5-year survivals ranging from 59% to 64%, which may be related to differences in patient characteristics. 19,20 Our 10-year survival of 31% is similar to the 37.6% reported by the UK Heart Valve Registry.…”
Section: Discussionmentioning
confidence: 95%
“…The 5-year survival in our study of PVE patients was only 37% AE 5% (non-PVE 63% AE 5%), which is similar to 30% AE 6% reported by Cortina and colleagues. 18 However, other studies have reported better 5-year survivals ranging from 59% to 64%, which may be related to differences in patient characteristics. 19,20 Our 10-year survival of 31% is similar to the 37.6% reported by the UK Heart Valve Registry.…”
Section: Discussionmentioning
confidence: 95%
“…Está demostrado que la necesidad de cirugía urgente en la endocarditis infecciosa es un importante factor predictor de mortalidad hospitalaria (11,(26)(27)(28). La mortalidad se incrementa de forma llamativa, de un 10-15% en el caso de cirugía electiva a un 35-45% en los pacientes que precisan cirugía urgente (11,(29)(30)(31)(32)(33)(34).…”
Section: 2-situacion Actual Del Problemaunclassified
“…Por ejemplo, en la escala EUROSCORE, la necesidad de una actuación "emergente" aumenta dos veces el riesgo de muerte en el postoperatorio y un estado preoperatorio "crítico" con necesidad de ventilación o inotrópicos previamente a la cirugía aumenta tres veces el riesgo quirúrgico.Además, el hecho de precisar cirugía durante la fase activa de la infección endocardítica aumenta más aún el riesgo de la intervención. De este modo en la escala EUROSCORE (51) la presencia de endocarditis activa en el momento de la cirugía eleva entre dos y tres veces más la mortalidad.Por lo tanto, los pacientes con endocarditis infecciosa que precisan cirugía urgente durante la fase activa de la infección tienen peor pronóstico, con una mortalidad hospitalaria claramente superior a los pacientes en los que la intervención quirúrgica se realiza de manera electiva(29)(30)(31)(32)(33)(34). Según diferentes estudios, la mortalidad de la endocarditis infecciosa intervenida de forma electiva se encuentra torno al 9% (30) y aumenta hasta el 25-35% si la cirugía urgente es necesaria(29)(30)(31)(32)(33)(34).Para intentar mejorar el pronóstico de estos pacientes el primer paso es identificar qué factores se asocian a mala evolución en los pacientes con endocarditis infecciosa izquierda que precisan cirugía urgente.El grupo de estudio está formado por 89 pacientes con endocarditis infecciosa izquierda que precisaron cirugía urgente, lo que supone un 23% de los pacientes con endocarditis infecciosa izquierda en nuestra serie.…”
unclassified
See 1 more Smart Citation